Poverty and Income Inequality in Nigeria: Any Causality? - Ogbeide, Evelyn Nwamaka Osaretin; Agu, David Onyinyechi (Asian Economic and Financial Review, 2015)
The issue of poverty has continued to pose serious threat to the continued cordial existence of an economy like Nigeria. Issues pertaining to poverty and inequality have also continued to receive wider attention among scholars in various economies of the globe. However, there seems to be a gap in literature as to the existence of a causal relationship between poverty and inequality. Should there be causality; the direction of causality is yet to be known, especially as it pertains to Nigerian economy. Therefore, this study seeks to establish whether or not there is a causal relationship between poverty and inequality in Nigeria. Adopting Granger causality techniques, this study finds out that there is a direct line of causality between poverty and inequality as well as indirect channels through unemployment and low life expectancy on inequality which exacerbate poverty in Nigeria.